Penerapan Pencatatan Akuntansi, Penyusunan Laporan Keuangan Pada UMKM - Syahputra, Jaka (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The study evaluated the methods of accounting and financial reporting on two SMEs in the fashion & accessories sector in Tempursari Village and SMEs handicrafts sector in Lebakharjo Village. The research method used is qualitative descriptive, with the use of observations, questionnaires, and direct interviews with SMEs owners Rendis Zalfa Olshop and Abyudaya Craft. The purpose of this research is to analyze the differences in methods of accounting recording and preparation of financial reports between the two SMEs, as well as their impact on financial management and decision-making. The results of the research showed that SMEs Rendis Zalfa Olshop implemented a modern approach using the Qasir application for accounting records, which allows for the preparation of structured and detailed financial reports. Instead, SMEs Abyudaya Craft continued to use a manual method with a cost book, which limits the clarity and regularity in the elaboration of the financial report. This difference in approach affects the analytical ability and efficiency in the financial management of both SMEs, where Rendi Zalfa Olshop is able to have a more detailed financial picture for more accurate decision-making, while Abyudaya Craft still faces limitations in terms of in-depth analysis of financial data.